Reading interest and attitude as correlates oi: students' performance in junior secondary school Yoruba language reading competence in Oyo state, Nigeria (2014)
Performance of students in Yoruba Language in both internal and public examinations is a serious concern which has attracted the attention of stakeholders of language education. In spite of different Research studies to investigate the cause and proffer solution, the problem persisted. It was on this basis, that this study investigated the extent to which reading interest and students' attitude account for students 'Yoruba language reading competency of Junior Secondary School Students in Oyo State. The study adopted non-experimental survey design. The sample consisted of one hundred and twenty Junior Secondary school students randomly selected within Ibadan Metropolis. Two instruments were used for data collection, namely; Reading Interest Scale in Yoruba Language (RISY) and Student Attitude Scale in Yoruba (SASY). The psychometric properties of the instrument used are: Reading Interest Scale in Yoruba Language (r = 0.8) and Students Attitude Scale in Yoruba (r = 0.8). Two research questions were generated and answered The data collected were analyzed using correlation and multiple repressions. The significance level was set at 0.05. The result revealed that the relationship among the predictor variables and the criterion variable is low. Hence, Attitude to Yoruba Language (r = 0.001, p> 0.05) and Reading Interest (r = 0.043, p>0.05) has a negative and low correlation with students' learning outcome in Yoruba Language. This indicates u weak significant and opposite relationship between the predictor variables and criterion variable. Based on these findings, it was recommended that teachers should update themselves through seminars and workshops from time to time on how to make Yoruba leading interesting to students so as to be able to correlate it with students learning outcomes. Schools, teachers and Guidance counselors should counsel students not only to associate reading Yoruba Language to tests, assignments and examination but that it should be a tool for relaxation, enjoyment, pleasure, self- development and advancement